2022
DOI: 10.1002/sstr.202200109
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress in 2D Metal–Organic Frameworks for Electrocatalysis

Abstract: The 2D nanosheets of metal–organic frameworks (MOFs) have recently emerged as a promising material that makes them valuable in widespread electrocatalytic fields due to their atomic‐level thickness, abundant active sites, and large surface area. Efficient electrocatalysts for hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and overall water splitting are highly desired with low overpotentials to promote the industrial applications of energy conversion and devices. 2D MOF nanostructures prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(89 citation statements)
references
References 152 publications
0
89
0
Order By: Relevance
“…Consequently, monolayer materials exfoliated from their corresponding bulk systems may possess unconventional properties in the fields of gas adsorption, 57 optics 58 and electrocatalysis. 59 EC-MOF monolayers can be synthesized through top-down or bottom-up approaches. Chemical exfoliation methods such as intercalation and electrochemical exfoliation are among the most common techniques in the top-down strategy.…”
Section: Thermodynamic Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, monolayer materials exfoliated from their corresponding bulk systems may possess unconventional properties in the fields of gas adsorption, 57 optics 58 and electrocatalysis. 59 EC-MOF monolayers can be synthesized through top-down or bottom-up approaches. Chemical exfoliation methods such as intercalation and electrochemical exfoliation are among the most common techniques in the top-down strategy.…”
Section: Thermodynamic Data Analysismentioning
confidence: 99%
“…58 On the contrary, bottom-up approach is a more efficient and convenient approach to build mono-layer materials by choosing ideal precursors, modulators and surfactants. 59 To shed light on the possibility of reaching at a mono-layer EC-MOF, we have calculated the inter-layer binding energies (E b ) according to Eq. 2 for all structures gathered in EC-MOF/Phase-I database.…”
Section: Thermodynamic Data Analysismentioning
confidence: 99%
“…[34][35][36][37][38][39] However, in the structure of MOFs, the metal nodes are surrounded by organic linking groups, 40 which limits their catalytic activity and conductivity; 41 thereby, it is vital to construct these structures with a rational design. [42][43][44][45] In terms of macrostructure control, 46 Lou et al typically construct a unique core-shell structure through chemical etching methods and other methods, 47 which could provide a larger catalytic interface area, 48 thereby significantly improving the electrocatalytic performance. 49 Li et al used carbonization to precisely regulate Hofmann-type MOFs into different forms (including nanosheets, nanoflowers, 50 nanotubes and aggregates), which OER catalytic performance far exceeds that of commercial RuO 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, constructing an artificial protective layer on Zn metal is necessary for stabilizing the electrode interface and suppressing the growth of Zn dendrites. [32,33] Recently, some works have reported that nano-CaCO 3 thin layer, [34] ZnF 2 coating [35] and other insulating protective layers prepared by the technology of atomic layer deposition [36] or direct covering [37] can effectively prolong the lifespan and improve cycling stability of Zn metal anode. However, due to the introduction of an additional layer on the Zn electrode, an annoying problem that prepared artificial protective layers usually deliver the sluggish transference of Zn ions may result in the increase of interfacial voltage polarization during the Zn deposition/dissolution process.…”
Section: Introductionmentioning
confidence: 99%